Enhancing Student Scientific Attitudes towards Civic Education Lesson through Inquiry-based Learning - Triyanto Triyanto (Intelektual Pustaka Media Utama, 2018)
The purpose of this study was to investigate student scientific attitudes toward civic education lesson through inquiry-based learning. The samples in this study were selected using stratified random sampling technique. Interactive data analysis consists of two stages: data collection and data display. The data were gathered by observation and interviews. Statistical results indicated that the student scientific attitudes towards civic education were a positive. Inquiry-based learning enhances student scientific attitude, where the most visible indicator of scientific attitudes is students' curiosity. Building scientific attitude can provide a logical solution to the problem student faced in their daily life and has scientific thinking skills. Creating and using science concepts related to students’ lives and interests will provide opportunities for a student to build their scientific attitude through meaningful learning activities. Scientific attitudes are grown through a series of experiences that students discover on their own during the learning process.